Pengaruh Perhatian Orang Tua Terhadap Akhlak Remaja Di Jorong Padang Tujuh Kanagarian Aua Kuniang Kec. Pasaman Kab. Pasaman Barat - Shelina Apriliani; Junaidi Junaidi; Charles Charles; Muhiddinur Kamal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research was motivated by the results of observations by researchers who found that there were teenagers who still received less attention from their parents so that they had poor morals. One of them was a teenager who went against his parents because the mother did not give him money to buy a quota and then the child said cruel words and even pushed his mother to the ground. The aim of this research is to find out concretely whether there is an influence of parental attention on the morals of teenagers in Jorong Padang Tujuh District. West Pasaman Regency. The theories used in this research are the theory of parental attention and the theory of adolescent morals. The type of research used in this research is a quantitative approach, the research plan used in this research is to use a correlational method. With a population of all Muslim teenagers aged 12-21 years (not married) in Jorong Padang Tujuh District. Pasaman Regency West Pasaman contains 137 people who will be taken as a sample of 25%, namely 34 people. The sampling technique used in this research was proportional random sampling. In this research, two instruments will be used, namely the parental attention instrument and the adolescent morals instrument. Based on the research results, it was obtained that r_count = 0.482, so the hypothesis was accepted which stated that there was a significant influence between parental attention and adolescent behavior, meaning that H_0 was rejected. This is because r_count = 0.482 which is in the coefficient interval 0.40-0.599 so that the level of correlation between the two variables is included in the medium category. The influence of parental attention on adolescent morals can be seen from the coefficient of determination between variables X and Y which is KD = 23.23%. This figure shows that 23.23% of adolescent morals are determined by parental attention and the rest is determined by other factors.